2015
DOI: 10.1136/bmjqs-2015-004001
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the AHRQ Community Pharmacy Survey on Patient Safety Culture: a factor analysis

Abstract: Background The U.S. Agency for Healthcare Research and Quality (AHRQ) developed a hospital patient safety culture survey in 2004, and has adapted this survey to other healthcare settings, such as nursing homes and medical offices, and most recently community pharmacies. However, it is unknown if safety culture dimensions developed in hospital settings can be transferred to community pharmacies. The aim of this study was to assess the psychometric properties of the Community Pharmacy Survey on Patient Safety Cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 27 publications
3
17
0
Order By: Relevance
“…In this study, the fifth thematic label was determined from four subthemes (Table 4), and are as follows: a) the healthcare environment influences patient safety, b) the way that it's done seems to backfire, c) communication, d) enough staffing, and e) teamwork and collaboration. Most of the responses from the participants of this study supported the results from the research conducted by Aboneh et al (2015) and Kieft et al (2014), which revealed the healthcare environment influenced patient safety.…”
Section: Research Question #2supporting
confidence: 78%
See 3 more Smart Citations
“…In this study, the fifth thematic label was determined from four subthemes (Table 4), and are as follows: a) the healthcare environment influences patient safety, b) the way that it's done seems to backfire, c) communication, d) enough staffing, and e) teamwork and collaboration. Most of the responses from the participants of this study supported the results from the research conducted by Aboneh et al (2015) and Kieft et al (2014), which revealed the healthcare environment influenced patient safety.…”
Section: Research Question #2supporting
confidence: 78%
“…According to Ritter (2011), healthcare settings should seek to understand the complex working environments and develop strategies that will improve the quality and safety of healthcare. Healthcare organizations that have safety cultures and work on evidence-based practice provide an HWE for the nurses and make continuous improvements on the culture of the organization (Aboneh, Look, Stone, Lester, & Chui, 2015).…”
Section: Problem Statementmentioning
confidence: 99%
See 2 more Smart Citations
“…This is in contrast to an overall score of excellent by 25% of our respondents. Aboneh [10] also used this community tool to assess pharmacy personnel perceptions of the safety culture in community, retail pharmacies in the United States. UF Health Shands has administered this AHRQ survey annually since 2012.…”
Section: Discussionmentioning
confidence: 99%